Energy and human resource development in developing countries : towards effective localization - Hickey, William (Senior consultant) (Palgrave Macmillan, 2017)
This book is about engaging and empowering people through their own domestic resources, by using upstream energy to create larger downstream employment opportunities. Incorporating sustainability, resource enhancement, and energy responsibility can generate awareness and better utilization of the resources and reduce reliance on foreign aid and economic development programs, which reinforce a North/ South consumption-based economy rather than empower the localized population. The author proposes a new paradigm of employee development, localized engagement, and empowerment for resource-rich developing Asian countries, based on the utilization and upbraiding of their resources in-situ. Here scholars, policymakers, and investors will find that human resource development (HRD) can structure constructive change through criterion-based education and reap economic prosperity.- Resumé vydavatel
Keywords: energetická politika -- rozvojové země; personální management -- rozvojové země; politika zaměstnanosti -- rozvojové země; energy policy -- developing countries; personnel management -- developing countries; manpower policy -- developing countries; elektronické knihy; monografie; electronic books; monographs